Literary Translation Universals: A Psycholinguistic Study of the Novice Translators' Common Choices - Zasiekin, Serhii (East European Journal of Psycholinguistics, 2014)
The paper outlines the study of translation S-universals and is based both on the psycholinguistic model of literary translation, which combines two approaches to language organization in today’s neuroscience – cognitivism and connectionism, and on the experimental data that demonstrate its validity. A free word association test was used to identify a translator’s cognitive style as a universal tendency determining his linguistic choice. This psycholinguistic tool helped explore the ways how the meaning of the original text was reconstructed in the target text by the selected group of novice translators. A quantitative content analysis and psycholinguistic text analysis were applied for the purpose of studying the correlation between specific textual features of authors and those of the translators. As the empirical study showed, the S-universals maintain the status of common strategies depending on translator’s cognitive style. A ‘think aloud protocol’ (TAP) analysis was used to explore the ways in which the meaning of the original text was reconstructed in the target text by the novice translators. A content analysis and psycholinguistic text analysis were applied for the purpose of studying the correlation between specific textual features of authors and those of translators. The results of the empirical study showed that the observed S-universals, while maintaining the status of common strategies, clearly depend on translator’s cognitive style (analytical or synthetic), and his dominant channel (visual, auditory, kinesthetic) of source text perception.ReferencesBerman, A. (1985). Traduction et la letter ou l’auberge du lointain. Paris: Seuil.Chesterman, A. (2004). Hypotheses about Translation Universals. In: Claims, Changes andChallenges in Translation Studies. Amsterdam: John Benjamins, 1-13.Chomsky, N. (1965). Aspects of the Theory of Syntax. Cambridge, Massachusetts: MIT Press.Klyukanov, I. (1987). Perevodcheskiye universalii i ikh psikholingvisticheskiy smysl[Translation universals and their psycholinguistic sense]. Perevodovedeniye i Kulturologia: Tseli,Metody, Rezultaty, 19 – 27.Krings, H. (1986). Was in den Kopfen von Űbersetzern vorgeht. Tűbingen: Narr.Lenk, U. (1998). Discourse Markers and Global Coherence in Conversation. Journal ofPragmatics, 30 (2), 245-257.Pápai, V. (2004). Explicitation: A Universal of Translated Text. In: Translation Universals. Dothey exist?. Amsterdam: John Benjamins, 143-164.Pitt, D. Mental Representation. The Stanford Encyclopedia of Philosophy. [Electronic resource].Retrieved 14.03.2013 from: http: //plato.stanford.edu/entries/mental-representation/.Poersch, J. (2007). Connectionism, a Challenging Task for Psycholinguistics in the NewCentury. In: Challenging Tasks for Psycholinguistics in the New Century. Katowice: University ofSilesia, 32-46.Schiffrin, D. (1987). Discourse Markers. Cambridge: Cambridge University Press.Sun, S. (2011). Think-Aloud-Based Translation Process Research: Some MethodologicalConsiderations. Meta: Translators’ Journal, 56 (4), 928-951.Toury, G. (1980). In Search of a Theory of Translation. Tel Aviv: Porter Institute of Semioticsand Poetics.Zasyekin, S. (2010). Translation as a Psycholinguistic Phenomenon. Journal ofPsycholinguistic Research, 39 (3), 225-234.Zasyekin, S. (2012). Psycholinguistic Modeling of Literary Translation Process. In: AppliedPsycholinguistics. Positive Effects and Ethical Perspectives. Milano: Franco Angeli, 334-342.
Keywords: translation; psycholinguistic model; translation universal; translator’s cognitive style; dominant channel of perception.